AI-DRIVEN MARKETING PERSONALIZATION AND CUSTOMER ENGAGEMENT: AN EMPIRICAL INVESTIGATION OF THE MEDIATING ROLES OF PERCEIVED VALUE AND CUSTOMER TRUST - Tio, Lina; Kulal, Salamiah Muhd; Yadewani, Dorris; Nanda, Ade Putra (LPPM Universitas Jambi, 2026)
While AI-based personalization is prevalent in e-commerce, the psychological processes underlying the transformation of these experiences into engagement remain under-theorized. The current study aims to examine a moderated-mediation model with perceived value and customer trust as parallel mediators and privacy concerns as moderator. We conducted a quantitative cross-sectional survey among 476 online consumers in Indonesia, Malaysia and Thailand. The data were analyzed using SmartPLS 4.0 using PLS-SEM, which includes measurement invariance testing and power analysis. The results confirm that AI-driven personalization significantly increases engagement directly and indirectly through perceived value (β=0.235) and trust (β=0.145). Interestingly, privacy concerns largely mitigate the trust-building path (β=−0.143). This research makes a novel contribution to the literature by empirically validating the “personalization-privacy paradox” in the emerging Southeast Asian market through a dual-pathway mediation lens. In practice, e-commerce operators should consider functional utility (value) as the main driver of engagement, while trust is a long-term relational outcome that needs transparent data governance.